Pengelolaan Komunikasi Interpersonal Di Sd Negeri 03 Karanganyar - Sularmi, Sularmi; , Prof. Dr. Sutama, M.Pd (2015)
While purpose of special of this research that is description about: 1) Planning of communications interpersonal in Elementary School State 03 Karanganyar; 2) Execution of communications interpersonal in Elementary School State 03 Karanganyar; 3) Umpanbalikan communications interpersonal in Elementary School State 03 Karanganyar. Research type is qualitative. Research approach applies phenomenology. Research subject is headmaster and teacher. Data collecting method applies in-depth interview, observation and documentation. Data analytical technique applies trianggulation. Result of research and solution: 1) Planning of communications interpersonal in Elementary School State 03 Karanganyar is more emphasizingly is balance of oral communications and written to be adapted for by requirement of school loading idea, message consignor, message receiver, and communication media; 2) Execution of communications interpersonal in Elementary School State 03 Karanganyar takes place in vertikal/upward, downwards, and harmonious horizontal communications especially in process of compilation of school workplan and execution of study causing haves a meaning (of) and continual; 3) Feedback of communications interpersonal in Elementary School State 03 Karanganyar takes place through giving of input and follow up in building organization of education of school, existence of considerations of school program and expansion of school can be mustered through feedback the communications. Keyword : communications, interpersonal, management